2020
DOI: 10.1186/s12917-020-02384-6
|View full text |Cite
|
Sign up to set email alerts
|

Culling reasons and risk factors in Estonian dairy cows

Abstract: Background: Culling is a major cost for dairy farms but also an essential part in managing herd productivity. This study aimed to identify the culling rates of Estonian dairy cows, identify the farmers' stated reasons and risk factors for culling. This observational study used registry data of all cows from herds with ≥20 cow-years in 2013-2015. Cow lactation-level analyses included data of 86,373 primiparous cows from 409 herds and 177,561 lactations of 109,295 multiparous cows from 410 herds. Weibull proport… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
40
2
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(51 citation statements)
references
References 52 publications
(74 reference statements)
7
40
2
2
Order By: Relevance
“…Longevity of dairy cows has been mostly evaluated in terms of culling of individual cows, as longevity is determined by the moment of the cows' departure from the herd for voluntary or involuntary reasons. Culling reasons and risk factors for culling are intensively studied worldwide [e.g., (21)(22)(23)]. Also studies on optimization of culling decisions and costs of culling (24-26) are performed.…”
Section: Discussionmentioning
confidence: 99%
“…Longevity of dairy cows has been mostly evaluated in terms of culling of individual cows, as longevity is determined by the moment of the cows' departure from the herd for voluntary or involuntary reasons. Culling reasons and risk factors for culling are intensively studied worldwide [e.g., (21)(22)(23)]. Also studies on optimization of culling decisions and costs of culling (24-26) are performed.…”
Section: Discussionmentioning
confidence: 99%
“…Culling is well-defined as the departure of animals from the herd because of reproductive problems, low milk production, or infection diseases [ 6 , 7 ]. Several dairy goats are culled due to reasons related to poor welfare provoked by infectious disease, udder or teats problems, infertility, feet and legs (lameness), mastitis, and non-conforming to specifications [ 8 ]. Commonly, there are two types of culling; (1) voluntary culling happens when the farmer selects to eradicate a healthy-fertile female due to low productivity, while (2) involuntary culling happens when the farmer is enforced to detach productive, profitable, females because of death, injury, infectious disease, infertility, or illness [ 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Over the last decades, culling reasons have altered. The percentage of culling owing to voluntary causes (e.g., delayed age at first kidding and low milk yield), has decreased and changed into more disease-related causes [ 8 , 10 ]. Involuntary culling is needed to decrease further suffering in individual animals, but a superior percentage of involuntary culling in the herd shows poor animal welfare and ineffective utilization of animal resources, which decreases sustainable dairy production [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Kvapilík et al (2016), udder diseases are the most common reasons for involuntary culling of dairy cows in the Czech Republic. Rilanto et al (2020) reported that udder disease is the second most common reason for culling, after foot and claw disorders. The improvement of cow treatment and herd management can lead to a decrease of the CM incidence in dairy herds.…”
Section: Introductionmentioning
confidence: 99%